A method for visualization of the variation of noncovalent interactions in crystal structures of conformational polymorphs. Issue 2 (6th April 2018) - Savchenkov, Anton V.; Serezhkin, Viktor N.
Abstract : A method for clear visualization of all, even the most imperceptible, noncovalent interactions and determination of their value in crystal structures is proposed. The application of the title method along with quantum‐chemical calculations offers opportunities for the correlation of potential energy of crystalline materials with noncovalent interactions in their crystal structures. Abstract : A method for clear visualization of the variation of noncovalent interactions in crystal structures of conformational polymorphs is developed and introduced. The first stage of the method establishes the characteristics of all, without exception, noncovalent interactions in all crystal structures under discussion. This is possible using a strict and objective method of construction of Voronoi–Dirichlet polyhedra within the framework of the stereoatomic model of crystal structures. The second stage of the method then involves plotting of diagrams, showing the relation between parameters characterizing interatomic interactions and chosen geometric parameters of molecules. Application of the title method to highly polymorphic systems of ROY and flufenamic acid allows several imperceptible features of real crystal structures to be revealed and determines the value of different types of interactions in their conformational polymorphs. The method is universal as it can be readily adapted to any system of crystal structures in which noncovalent interactions change as a function of any parameters. Employment of the title method along with quantum chemical calculations offers opportunities for the correlation of potential energy of crystalline materials with noncovalent interactions in their structures, which is a giant step forward towards a more complete understanding of the relationship between the structure and properties of compounds.